2016
DOI: 10.3389/fmicb.2016.00102
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and Anti-Infection of a Marine Bacterial Exopolysaccharide Against Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a well-known pathogenic bacterium that forms biofilms and produces virulence factors, thus leading to major problems in many fields, such as clinical infection, food contamination, and marine biofouling. In this study, we report the purification and characterization of an exopolysaccharide EPS273 from the culture supernatant of marine bacterium P. stutzeri 273. The exopolysaccharide EPS273 not only effectively inhibits biofilm formation but also disperses preformed biofilm of P. aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 55 publications
(76 reference statements)
3
98
0
Order By: Relevance
“…The CaCO 3 -producing medium was prepared as following: nutrient broth (3 g), NaHCO 3 (2.12 g), NH 4 Cl (10 g), CaCl 2 (16.65 g), urea (20 g) and agar (15 g) in one liter filtered seawater. Genomic DNA was extracted from the isolate, and PCR (polymerase chain reaction) was performed to amplify the 16S rDNA gene sequence as described previously with universal primers 27F (5′-AGAGTTTGATCCTGGCTCAG-3′) and 1492R (5′-AAGGAGGTGATCCACCC-3′) (Wu et al, 2016). To determine the phylogenetic position of the B. linens BS258, the 16S rDNA gene sequence was analyzed by the BLAST programs 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The CaCO 3 -producing medium was prepared as following: nutrient broth (3 g), NaHCO 3 (2.12 g), NH 4 Cl (10 g), CaCl 2 (16.65 g), urea (20 g) and agar (15 g) in one liter filtered seawater. Genomic DNA was extracted from the isolate, and PCR (polymerase chain reaction) was performed to amplify the 16S rDNA gene sequence as described previously with universal primers 27F (5′-AGAGTTTGATCCTGGCTCAG-3′) and 1492R (5′-AAGGAGGTGATCCACCC-3′) (Wu et al, 2016). To determine the phylogenetic position of the B. linens BS258, the 16S rDNA gene sequence was analyzed by the BLAST programs 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyl radical-scavenging activity The hydroxyl radical-scavenging activity of EPS was determined according to the method described by Wu et al (31), with few modifications. In brief, PBS (20 mM, pH 7.4), 50 μL; 12.5-mM 1,10-phenanthroline solution, 25 μL; 2.5-mM FeSO 4 solution, 25 μL; and 20-mM H 2 O 2 , 25 μL were added successively to each well of 96-well plates and mixed thoroughly.…”
Section: Antioxidant Activity Of Epsmentioning
confidence: 99%
“…Given its capacity for antioxidant activity, we next decided to test whether EPS-NA3 also exhibited the ability to inhibit biofilm formation (31), given the role of EPS in preventing colonization by competing bacteria. Observation by fluorescence microscopy of B. cereus (Figs.…”
Section: In Vitro Anti-biofilm Activities Of Eps-na3mentioning
confidence: 99%
“…Allesen-Holm et al (2006) reported that P. aeruginosa biofilm produces a large amount of eDNA in the late-log phase (4-10 h) of growth. Thus, eDNA could represent a key target for anti-biofilm strategies, by disabling biofilm establishment or disrupting the structure at early stages (Martins et al 2010, Wu et al 2016. Macrophages are the primary innate immune cell that participate in chronic periapical lesions (Nair 2004).…”
Section: Ramirez Et Al Inflammatory Potential Of Biofilm Componentsmentioning
confidence: 99%